2017
DOI: 10.4103/sni.sni_478_16
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative steroids for lumbar disc surgery: A meta-analysis of randomized controlled trials

Abstract: Background:Our review question was “Does perioperative steroids administration, in comparison with other treatments or placebo, improve either postoperative pain control, length of hospital stay, or return to work in patients undergoing lumbar disc surgery?”Methods:We searched PubMed, CINAHL PLUS, and Cochrane databases for randomized control trials (RCTs) studying the role of steroids for lumbar disc surgery. Studies that compared perioperative steroids with other treatments or placebo were included. Study ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…[ 18 , 19 ] One meta-analysis reported that intraoperative ESI application offers some benefits in pain control with a significant reduction in the length of hospital stay. [ 20 ] The most recent meta-analysis indicated a lower back and leg pain score, decreased morphine consumption, and shorter hospital stay without difference in complications for ESI application compared to placebo after lumbar discectomy in lumbar disc herniation that was not detected in previous meta-analyses. [ 21 ] However, these meta-analyses still have many limitations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 , 19 ] One meta-analysis reported that intraoperative ESI application offers some benefits in pain control with a significant reduction in the length of hospital stay. [ 20 ] The most recent meta-analysis indicated a lower back and leg pain score, decreased morphine consumption, and shorter hospital stay without difference in complications for ESI application compared to placebo after lumbar discectomy in lumbar disc herniation that was not detected in previous meta-analyses. [ 21 ] However, these meta-analyses still have many limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis currently published [ 24 - 26 ] showed that it is safe to inject epidural steroids during lumbar spine surgery. According to the search, there was no meta-analysis on the outcomes of using epidural steroids after PTED, so this study is the first.…”
Section: Discussionmentioning
confidence: 99%
“…Computer navigation technology is “designed to improve the surgical performance and clinical outcome of knee replacement surgery,” and with this in mind, its use has increased in recent years. [ 15 20 ] In parallel, the volume of literature relating to computer navigation technology in this field has expanded greatly, most published work relating to component alignment, whereas very few studies have addressed functional outcome. [ 21 24 ] Thus, in this protocol, we designed a randomized controlled trial to compare implant alignment, functional scores, and survival of the implant using computer-assisted surgery versus a conventional surgical technique.…”
Section: Discussionmentioning
confidence: 99%